THE METHOD OF HIGH-ACCURE MEASUREMENT OF DIRECTIONS WITH AN ELECTRONIC TACHOMETER - Марущак, Михайло (SWorldJournal, 2024)
The paper presents a method of high-precision direction measurement with an electronic tachometer. It is proposed to equip the tachometer reflector with a horizontal base and measure the directions at three points of the base, which will allow to determi